2010
DOI: 10.1007/s10336-010-0520-1
|View full text |Cite
|
Sign up to set email alerts
|

Pigment limitation and female reproductive characteristics influence egg shell spottiness and ground colour variation in the house sparrow (Passer domesticus)

Abstract: One of the hypotheses to explain egg colour variation in birds lays in the context of sexual selection, where egg colour may signal the female's physical condition and antioxidant capacity. We tested one of the assumptions following from this hypothesis, that eggshell pigment deposition should be limited for females. The study was conducted in a captive house sparrow (Passer domesticus) population over several years under constant environmental conditions. This multi-brooded species lays eggs which vary in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Moreover, Blue Tit and House Sparrow females that laid larger clutches laid eggs with a more even distribution of spots García-Navas 2009, López de Hierro andDe Neve 2010). In studies of Eurasian Kestrels (Martínez-Padilla et al 2010), British Great Tits (Stoddard et al 2012) and Eurasian ReedWarblers (Krištofík et al 2013), no significant relationships between eggshell spot color and clutch size were found.…”
Section: Eggshell Spotting and Female Traitsmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, Blue Tit and House Sparrow females that laid larger clutches laid eggs with a more even distribution of spots García-Navas 2009, López de Hierro andDe Neve 2010). In studies of Eurasian Kestrels (Martínez-Padilla et al 2010), British Great Tits (Stoddard et al 2012) and Eurasian ReedWarblers (Krištofík et al 2013), no significant relationships between eggshell spot color and clutch size were found.…”
Section: Eggshell Spotting and Female Traitsmentioning
confidence: 94%
“…Others determined pigment concentration of the eggshell by chemical analysis (Maurer et al 2011b, Cassey et al 2012, Duval et al 2013, Brulez et al 2014, or analyzed digitized pictures of eggshells to determine the percentage of spotted eggshell surface (Martínez-de la Puente et al 2007, Sanz and García-Navas 2009, Bulla et al 2012, Holveck et al 2012, Brulez et al 2014), or to determine hue, saturation, and brightness derived from HSB and RGB (Martínez-Padilla et al 2010, Cassey et al 2012, Holveck et al 2012), or to determine other spotting pattern variables, such as pattern contrast and marking size (Stoddard et al 2012). Finally, many studies used visual scoring of photographs, and spotting pattern was expressed as spot intensity, spot size, and spot distribution (Gosler et al 2005, Sanz and García-Navas 2009, López de Hierro and De Neve 2010, Bulla et al 2012, Holveck et al 2012, De Coster et al 2013, Hargitai et al 2013, Brulez et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…red) eggs because of an increase in egg size, but there was no proportionate change in the quantity of pigment deposited over the eggshell surface (Odabaşi et al, 2007). In the house sparrow (Passer domesticus), pigment deposition would decrease with age and through the laying sequence (López de Hierro and De Neve, 2010). Furthermore, a cross-fostering experiment in house wrens (Troglodytes aedon) showed that less-pigmented eggshells indicated heavier eggs and higher female body condition (residuals from a regression of body mass on tarsus length) (Walters and Getty, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, earlier-laid host eggs may be removed preferentially in comparison with the later-laid eggs, which are usually paler [47,48]. Moreover, cuckoos could nonrandomly predate on host eggs of a particular type.…”
Section: (C) Statistical Analysesmentioning
confidence: 99%